Faktor Yang Mempengaruhi Minat Pembelian Smartphone Apple Pada Mahasiswa/I Fakultas Ekonomi Universitas Tarumanagara - Marvin Louis; Carunia Mulya Firdausy (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this research is to examine whether 1) perceived product quality, electronic word of mouth, and perceived price influence the purchase intention of students who use apple smartphones at the Faculty of Economics at Tarumanagara University. The population of this research is students who use apple smartphones at the Faculty of Economics at Tarumanagara University. The sample is 100 respondents with an online questionnaires with nonprobability sampling technique with purposive sampling. Overall the results of this study are 1) perceived product quality has a positive effect on purchase intention in buying Apple smartphones among students at the Faculty of Economics, Tarumanagara University. 2) electronic word of mouth has a positive effect on purchase intention in buying Apple smartphones among students at the Faculty of Economics, Tarumanagara University. 3) the perception of prices has a positive effect on purchase intention in buying Apple smartphones among students at the Faculty of Economics, Tarumanagara University. 4) perceived product quality, electronic word of mouth, and perceived price together have a positive effect on purchase intention in buying Apple smartphones among students at the Faculty of Economics, Tarumanagara University. Tujuan dari penelitian ini adalah untuk menguji apakah 1) persepsi kualitas produk, elektronik dari mulut ke mulut, dan persepsi harga mempengaruhi niat pembelian siswa yang menggunakan smartphone apel di Fakultas Ekonomi di Universitas Tarumanagara. Populasi penelitian ini adalah siswa yang menggunakan ponsel cerdas apel di Fakultas Ekonomi di Universitas Tarumanagara. Sampel penelitian adalah 100 responden dengan kuesioner online dengan teknik nonprobability sampling dengan purposive sampling. Secara keseluruhan hasil penelitian ini adalah 1) persepsi kualitas produk berpengaruh positif terhadap niat beli smartphone Apple di kalangan mahasiswa di Fakultas Ekonomi, Universitas Tarumanagara. 2) elektronik dari mulut ke mulut memiliki efek positif pada niat beli dalam membeli smartphone Apple di kalangan mahasiswa di Fakultas Ekonomi, Universitas Tarumanagara. 3) persepsi harga memiliki efek positif pada niat beli dalam membeli smartphone Apple di kalangan mahasiswa di Fakultas Ekonomi, Universitas Tarumanagara. 4) persepsi kualitas produk, kata elektronik dari mulut ke mulut, dan harga yang dipersepsikan bersama-sama memiliki efek positif pada niat beli dalam membeli ponsel cerdas Apple di kalangan mahasiswa di Fakultas Ekonomi, Universitas Tarumanagara.